The chilldren at green meadows - Blyton, Enid. (b)
Francis, Clare and Sam would love to have animals of their own, but since their father was hurt in the war it's a struggle for their poor mother to just keep the big house at Green Meadows ticking over. But when a new block of flats with a strict no-animal policy opens near by, they soon find themselves with an exciting secret and Green Meadows is rapidly filled with animals and laughter once more.
Keywords: Families -- Juvenile fiction; Animals -- Juvenile fiction; Animals